Assessing the quality of published clinical trials regarding the effect of conservative methods in women with pelvic floor disorders using CONSORT tool - Zahra Hadizadeh-Talasaz; Mona Larki; Robab Latifnejad Roudsari (Mashhad University of Medical Sciences, 2023)
Introduction: When designing an evidence-based treatment program to help patients with pelvic floor disorders through conservative methods, it is necessary to select studies that, in addition to focusing on the desired subject, also have a suitable quality. Therefore, the present study was performed with aim to assess the quality of published clinical trials regarding the effect of conservative methods in women with pelvic floor disorders using CONSORT tool. Methods: In this critical review, published RCTs which are indexed in PubMed, Scopus, Medline, Cochrane، Web of Science as well as Persian databases such as SID and Magiran from 2001 to 2021 were searched using Persian and English keywords. Out of 416 articles, 64 RCTs were assessed using CONSORT 2017 checklist. Data were analyzed using SPSS (version 16) and descriptive statistical tests. Results: In the complete assessment of the articles, the mean overall score of articles quality based om CONSORT criteria was 28.85 ± 7.5 (minimum and maximum range of 12-41). Title, introduction, objectives and discussion had the highest mean score; whereas method and results section had the lowest mean score. Also, 33.9% of the articles had not point out the type of the article in the title. In the abstract section, 75% of the articles did not report the study type, 87.5% did not describe the method of randomization, and more than 73.2% did not report blinding. Conclusion: The appraised articles in the present study had a moderate quality. Improving the quality of clinical trials, especially in the method section, is essential for more use at the bedside and providing better care. Getting help from experts in the statistics and methodology as well as using standard tools for critical appraisal, the quality of articles could be improved.